HUBUNGAN ANTARA PENGETAHUAN TENTANG JAMU HAMIL DENGAN KONSUMSI JAMU PADA IBU HAMIL DI KELURAHAN KARANGKLESEM KECAMATAN PURWOKERTO SELATAN TAHUN 2019 - ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Herb is a traditional medicine derived from ingredients or ingredients in the form of plant, animal, mineral, sarian preparations used for treatment. The practice of consuming herbal medicine has been going on for generations, as well as the consumption of herbal medicine for pregnant women which aims to eliminate nausea, vomiting, fatigue and weakness, strengthen the fetus and calm the mind. Side effects caused include miscarriages, fetal heart abnormalities and the skin of the fetus is layered or crusted because of the sediment of herbs, and the placenta becomes sticky. The objective of this study was to determine the relationship between knowledge about pregnant herbs and the use of herbs during pregnancy. Research method: This study uses explanatory surveys. The total population is 40 mothers in the Karangklesem village, South Purwokerto. The sampling technique is random sampling. Data analysis using the chi square test with a degree of confidence p = 0.05. The results showed that the majority of pregnant women had poor knowledge about herb which was equal to 75%, the majority of pregnant women consuming herb during pregnancy that is equal to 60%, and there was a significant relationship between maternal knowledge with herbal consumption during the pregnancy. The conclusion is that there is a relationship between mother's knowledge about herb and the consumption of herb during the pregnancy. Keywords: knowledge, consumption of herb during pregnancy